Cryo-EM of macromolecular assemblies at near-atomic resolution - Baker, Matthew L (2010)
With single-particle electron cryomicroscopy (cryo-eM), it is possible to visualize large, macromolecular assemblies in near-native states. although subnanometer resolutions have been routinely achieved for many specimens, state of the art cryo-eM has pushed to near-atomic (3.3–4.6 Å) resolutions. at these resolutions, it is now possible to construct reliable atomic models directly from the cryo-eM density map. In this study, we describe our recently developed protocols for performing the three-dimensional reconstruction and modeling of Mm-cpn, a group II chaperonin, determined to 4.3 Å resolution. this protocol, utilizing the software tools eMan, Gorgon and coot, can be adapted for use with nearly all specimens imaged with cryo-eM that target beyond 5 Å resolution. additionally, the feature recognition and computational modeling tools can be applied to any near-atomic resolution density maps, including those from X-ray crystallography.